Chinese specific characteristics of sporadic Creutzfeldt-Jakob disease: a retrospective analysis of 57 cases. - Wei Zhao (Public Library of Science (PLoS), 2013)
Objective Sporadic Creutzfeldt-Jakob disease (sCJD) is a fatal and transmissible neurodegenerative disorder. However, no studies have reported Chinese specific characteristics of sCJD. We aimed to identify differences in sCJD between Chinese patients and patients from other countries. Methods The data from 57 Chinese sCJD patients were retrospectively analyzed, including demographic data, clinical manifestations, laboratory examinations, electroencephalograms (EEGs), diffusion-weighted imaging (DWI) scans, positron emission tomography (PET) scans, and pathological results. Result The disease was pathologically confirmed in 11 patients. 39 cases were diagnosed as probable sCJD, and 7 were possible. Of the total cases, 33 were male, and 24 were female. The onset age ranged from 36 to 75 years (mean: 55.5, median: 57). Disease onset before the age of 60 occurred in 57.9% of patients. The disease duration from onset to death ranged 5-22 months (mean: 11.6, median: 11), and 51.9% of patients died 7 to 12 months after disease onset. The majority of patients presented with sub-acute onset with progressive dementia. 3 of the 9 patients who took 14-3-3 protein analysis had positive results (33.3%). The sensitivity of EEG was 79.6% (43/54). For DWI and PET examinations, the sensitivities were 94% (47/50) and 94.1% (16/17), respectively. In seven patients who did not show typical hyper-intensities on the first DWI examination, abnormalities of hypo-metabolism in the cerebral cortex were clearly detected by PET. In 13 out of the 17 patients, PET detected extra abnormal regions in addition to the hyper-intense areas observed in DWI. Conclusion This is the first study to indicate that Chinese sCJD patients have a much earlier onset age and a longer disease duration than other populations, which is most likely related to racial differences. The longer disease duration may also be a probable characteristic of Asian populations. PET had high sensitivity for the diagnosis of sCJD.